Endocopic diverticuloesophagotomy in dysphagia of combined genesis in aged patient (сlinical case) - I. E. Sudovykh; E. A. Drobyazgin; Yu. V. Chikinev (Сибирский научный медицинский журнал, 2020)
Zenker’s pharyngeal-esophageal diverticulum is more common in elderly patients, manifests itself with dysphagia and is dangerous with aspiration complications. The clinical case describes a combination of the first detected large Zenker diverticulum, pneumonia, neurological symptoms in an 86-year-old patient with aphagia. Despite the combination of aggravating factors, oral endoscopic ventriculostomy was performed using a flexible endoscope. After surgery: there are no violations of the act of swallowing. The patient eats liquid and semi-liquid food. No complaints of dysphagia were presented. At x-ray control, there is some delay of the contrast agent in the diverticulum, which does not prevent its emptying. The case demonstrates the effectiveness of endoscopic intervention in large-sized Zenker diverticulum, the possibility of its implementation in age-related patients with combined pathology, including neurological deficiency, preserving the patient’s chance of recovery.